Dieu au Collège de France - Compagnon, Antoine; Surprenant, Céline (Passage des disciplines, 2023)
Dieu au Collège de France, volume 6 of the « Passage des disciplines » series, includes texts that were presented during the symposium "Dieu at the Collège de France", which was held in June 2021, after the delays caused by the pandemic, as part of "Passage des disciplines. Global history of the Collège de France, 19th-20th century". This research program and the series associated with it examines the genesis of scientific and literary fields of knowledge, their mapping and their evolution during the 19th and 20th centuries, on both national and international levels, from the standpoint afforded by the history of the renewal of academic chairs at the Collège de France. "Dieu" is, to be sure, not a new 19th discipline, or a "founder of discursivity", as Foucault called the scholars who had invented not only new discourses, but, more broadly, discursive continents, new "épistemes". God is certainly an ancient "inventor of discursivity" and the discursive continent that he has launched is considerably more diffuse than those which come from Freud, Darwin, Einstein or Durkheim, which were the object of preceding symposia, and, for the first three ones, of the first three volumes of the series. Yet, it seemed to us possible to examine, in collaboration with Thomas Römer, holder of the chair The Hebrew Bible and its Contexts, the science of God and how the Collège de France, at different times of its history, and through this institution, the university, higher education in general, the life of ideas, made way for the sciences of religion.